2021
DOI: 10.1155/2021/6638897
|View full text |Cite
|
Sign up to set email alerts
|

Digital‐Twin‐Based Evaluation of Nearly Zero‐Energy Building for Existing Buildings Based on Scan‐to‐BIM

Abstract: In recent years, the global energy environment has become increasingly severe, and the problems such as global warming, soaring carbon emissions, and excessive use of petrochemical energy have attracted increasing attention from all walks of life. The construction industry, which accounts for about 30% of the total energy consumption, needs to effectively manage and use renewable energy. The application of building information model (BIM) in the evaluation of retrofitting schemes of existing buildings is one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 28 publications
(32 reference statements)
0
11
0
2
Order By: Relevance
“…Therefore, proposed a new hierarchy flow chart for a digital model to emphasize the technical and financial viability of NZEB for existing facilities. In addition, Zhao et al (2021) proposed a technique that uses scan-to-BIM and DT to evaluate NZEB retrofitting schemes by analyzing energy consumption and carbon emission indicators of existing facilities using scan-to-BIM and DT. Urban planning and policy decisions can be modeled using the data generated by DT.…”
Section: Planning Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, proposed a new hierarchy flow chart for a digital model to emphasize the technical and financial viability of NZEB for existing facilities. In addition, Zhao et al (2021) proposed a technique that uses scan-to-BIM and DT to evaluate NZEB retrofitting schemes by analyzing energy consumption and carbon emission indicators of existing facilities using scan-to-BIM and DT. Urban planning and policy decisions can be modeled using the data generated by DT.…”
Section: Planning Phasementioning
confidence: 99%
“…Pan and Zhang (2021) recommend future researchers use information fusion by collecting and merging multiple sources of monitoring data. Moreover, Zhao et al (2021) suggested that researchers should apply more retrofitting technologies to existing buildings and provide more financial data as well as more data integration into the established BIM. Liu et al (2021) recommended that more validation data samples should be collected.…”
Section: Future Directionsmentioning
confidence: 99%
“…Compared to other general techniques like a total station, the main advantage of terrestrial laser scanning is the fast collection of high-density points with x, y, z coordinates and RGB and intensity values, which can be further used in reconstructing a 3D model of objects in construction environments. With the development of TLS and modeling approaches, relevant studies have been conducted on the reconstruction of different objects, including buildings [ 49 , 51 , 53 , 54 , 58 , 60 , 61 , 65 , 70 , 72 ], civil infrastructure and its components (bridges [ 55 , 62 , 63 , 64 , 73 , 74 , 75 , 76 , 77 ], tunnels [ 50 ], precast concrete elements [ 71 , 79 ], removable floodwalls [ 56 ], bridge piers [ 66 ], pipe racks [ 52 ]), and construction sites [ 67 , 68 , 69 ]. The process of 3D model reconstruction using TLS can be classified into three main phases: (1) data collection, (2) data pre-processing, in which the critical task is to register multiple scans in a common coordinate system, and (3) modeling.…”
Section: Research Topics Related To Tls In the Aec Industrymentioning
confidence: 99%
“…Cui et al [4] presented a method that couples linear structures with three-dimensional surfaces to automatically reconstruct 3D models of indoor environments using point cloud data from mobile laser scanning. Zhao et al [5] used 3D laser scanning to efficiently create the building energy model of existing buildings and to identify and evaluate the feasibility of existing building retrofitting schemes. Kim et al [6] used BIM, 3D laser scanning, and intelligent algorithms for automated spatial analysis to help solve the problems derived from arrangement and installation of complex structures.…”
Section: Introductionmentioning
confidence: 99%